2021
DOI: 10.1111/tbed.14381
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibility of eastern cottontails and New Zealand white rabbits to classical rabbit haemorrhagic disease virus (RHDV) and RHDV2

Abstract: Rabbit haemorrhagic disease virus (RHDV) is associated with high morbidity and mortality in the European rabbit (Oryctolagus cuniculus). In 2010, a genetically distinct RHDV named RHDV2 emerged in Europe and spread to many other regions, including North America in 2016. Prior to this study it was unknown if eastern cottontails (ECT(s); Sylvilagus floridanus), one of the most common wild lagomorphs in the United States, were susceptible to RHDV2. In this study, 10 wild-caught ECTs and 10 New Zealand white rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…15 Furthermore, cottontails (Sylvilagus spp), which are susceptible to disease but do not always die after infection, are prolific across the country and can be in close contact with domestic rabbits in certain situations, particularly those that live as pets in backyards. 4 Clearly, the best means of preventing mortality is vaccination, and the lack of a readily available vaccine in the United States is concerning for rabbitries, pet owners, and wildlife managers. Thus, the vaccine described herein is timely and will be useful to prevent further infections of rabbits in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Furthermore, cottontails (Sylvilagus spp), which are susceptible to disease but do not always die after infection, are prolific across the country and can be in close contact with domestic rabbits in certain situations, particularly those that live as pets in backyards. 4 Clearly, the best means of preventing mortality is vaccination, and the lack of a readily available vaccine in the United States is concerning for rabbitries, pet owners, and wildlife managers. Thus, the vaccine described herein is timely and will be useful to prevent further infections of rabbits in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…3 Disturbingly, RHDV2 has a wider host range than classic RHDV, encompassing varieties of wild rabbits previously thought to be unaffected by RHDV, including European and other hares (Lepus spp) and wild rabbits native to the American continent within the genus Sylvilagus. [2][3][4][5] In 2016, the first cases of RHDV2 were reported in North America. The virus was initially detected in…”
mentioning
confidence: 99%
“…(2015) detected an EBHSV‐infected eastern cottontail during an EBHS outbreak in Italy, and subsequently reproduced the disease in one out of four eastern cottontails inoculated with EBHSV, but not in those inoculated with classic RHDV. A recent study performed at Plum Island Animal Disease Center (New York, USA) with eastern cottontails demonstrated that this species is susceptible to RHDV2, since three out of five experimentally infected individuals died with typical lesions and both viral RNA and antigen were detectable in several tissues (Mohamed et al., 2018). Our data are still limited, but suggest that desert cottontails develop disease when they are naturally infected with RHDV2; however, a certain degree of resistance in animals of the genus Sylvilagus cannot be totally excluded.…”
Section: Discussionmentioning
confidence: 99%
“…At least some of the variation in the reported mortality rates for RHDV2 may be related to host age and infectious dose [ 29 ]. However, recent experimental work suggests that the case fatality rate can reach 100% in rabbits [ 20 , 32 ]. Mohamed et al [ 32 ] undertook a comparative experimental study on the effects of RHDV2 on wild caught eastern cottontail ( Sylvilagus floridanus ) relative to New Zealand white rabbits (NZWR), and demonstrated that cottontails had lower disease-induced mortality in comparison with NZWR.…”
Section: Ecological Risk To Irish Hares Of the Emergence Of Rhdv2mentioning
confidence: 99%
“…Animals typically die within 48–96 hours of being exposed to the pathogen. The viral load is high in infected animals that succumb, based on the low Ct value observed by real-time reverse transcription–polymerase chain reaction (RT-PCR) (e.g., [ 32 ]). Death without clinical signs can occur.…”
Section: Introductionmentioning
confidence: 99%